Swot dimensional analysis for strategic planning – the case of overseas real estate developers in Guangzhou, China - Y. P. Leung, Barbara; C. M. Hui, Eddie; Tan, Jian-hui; Chen, Lin; Xu, Wei-bin (International Journal of Strategic Property Management, 2011)
China has been attracting overseas real estate developers (OREDs) with its expanding real estate market since the adoption of the Open Door Policy. This attractiveness has been enhanced by China's accession to the World Trade Organization and the Closer Economic Partnership Arrangement and is likely to remain for the foreseeable future. However, OREDs to conduct developments in China which adopts a socialist market-oriented approach is not without difficulties. The study has developed a SWOT dimensional analysis technique which is able to integrate the strengths and weaknesses of OREDs and also the opportunities and threats found in the market for formulating their (s)trategic plans and market positions. Apart from proposing a holistic model for OREDs’ strategic planning, the findings also suggested that OREDs in Guangzhou are in general strong in management and financial capacity but weak in understanding the market conditions. Building up a localized management team which understands the market and has good connection with local officials and business peoplė is of prime concerns.First Publish Online: 4 Jul 2011